Voltage Restoration of Islanded Microgrids via Cooperative Second-Order Sliding Mode Control*. Issue 1 (July 2017) - Pilloni, Alessandro; Pisano, Alessandro; Usai, Elio
Abstract: In this paper we address the problem of voltage restoration and control of inverter-based islanded microgrid. The problem is attacked from a multi-agent systems consensus-based perspective at the microgrid's secondary control layer. An ad-hoc chattering-free second-order sliding-mode controlled is designed to achieve voltage restoration in a distributed way while enhancing the underlying system's robustness. With respect to existing solutions, the proposal do not require neither the knowledge of any grid parameter nor model-based information on the distributed generators. Performance of the proposed control system is analyzed by Lyapunov tools, and a simple set of tuning rules, guaranteeing the achievement of exact finite-time voltage restoration, are obtained. Computer simulations support the effectiveness of the strategy.